Application of distraction osteogenesis in managing bone cysts - Verdiyev, Vagif (Springer International Publishing, 2013)
BACKGROUND: Despite the great amount of research concerning bone cysts, there is still no commonly accepted method of treatment. The aim of this study was to evaluate the effectiveness managing bone cyst with hybrid external fixator by distraction osteogenesis. MATERIALS AND METHODS: Between 1982 and 2009, 25 patients with unicameral (20 patients) and aneurismal (five patients) bone cysts were treated using this method. Eighteen patients had a history of pathological fracture at the same location. Cysts were located in the humerus, femur, tibia, and radius. Median follow-up was 48 (range 31–91) months. Results were evaluated on plain radiographs according to the classification system of Capanna et al. Functional assessment was done using the modified system recommended by Enneking et al. RESULTS: In our study group of 25 bone cysts, 15 were classified as completely healed and nine as healed with residual radiolucency. Recurrence was observed in one patient. Absence of response to treatment was not observed. All patients had excellent functional outcomes, except one with recurrence who was rated poor. CONCLUSIONS: As bone cysts are found in long bones in 90–95 % of patients, and taking into account our achieved positive results in almost all patients, we recommend this method of distraction osteogenesis as a treatment option. It is an effective, economical method of treatment, which eliminates deformity and restores bone length, especially in patients with pathologic fractures.